A unified multi-functional on-board EV charger for power-quality control in household networks. (1st April 2018) - Taghizadeh, Seyedfoad; Hossain, M.J.; Lu, Junwei; Water, Wayne
Highlights: Designing a feasible unified control system for a multifunctional on-board EV charger. The EV charger can operate in V2G/G2V mode as its main function. The EV charger can simultaneously perform three ancillary functions of a STATCOM and an APF. Stress on the EV battery is reduced using a two-leg buck-boost DC/DC converter. Simulation and experimental results verify the efficacy of the proposed system. Abstract: This paper presents a feasible and reliable unified control system for a single-phase 4.5 kVA on-board multifunctional electric-vehicle (EV) charger that is connected to a low-voltage household network. Based on the proposed control system, the EV charger can operate as both a single-phase four-quadrant static synchronous compensator (STATCOM) and an active power filter (APF). The proposed EV charger can simultaneously perform four functions: charging/discharging the electric-vehicle's (EV's) battery; reactive power compensation; voltage regulation; and, harmonic reduction, which are important concerns of the existing power grid. Accordingly, it can enhance the building s voltage profile, power quality, and reliability, which makes the proposed method a complete solution for low-voltage household networks. The stress on the EV battery is also reduced, which can enhance its lifetime. A stability analysis of the proposed unified control system is provided in this paper. The simulation results, with two loads, static and dynamic, confirm the efficacy and reliability of the proposed system. The performance of the designed unified control system is also validated by experimental results.